BADAN PENELITIAN DAN PENGEMBANGAN DAERAH SEBAGAI THINK TANKS UNTUK MENGAKSELERASI PERUBAHAN PERADABAN DI ERA DIGITAL - Herie Saksono (Jurnal Kebijakan Pembangunan, 2019)
The digital era was marked by the advancement of digital technology devices, the presence of big data, the digitization process, and its intensive and massive use. Digitalization can save time, eliminate natural boundaries, integrate space and time at one and the same moment, and ultimately change civilization, facilitate life, and prosper human beings. The implementation of regional government affairs requires the ability of local governments (local governments) to adapt, accelerate, and ensure the quality of services in accordance with the rhythms and civilizations of the digital era. Responding to this dynamic, the regional government is given the authority to support government affairs in the field of research and development. Ideally, research and development are carried out by regional instruments that are independent and focused on managing research and development. The Regional Research and Development Agency (BPPD) as a think tank has a strategic role in carrying out regional government affairs including fostering and supervising the implementation of regional government through the function of research and development. This study seeks to uncover the existence of local government think tanks in the Province of South Kalimantan. The method used is qualitative-descriptive with a focus on the BPPD study in South Kalimantan Province. The results of the analysis and discussion concluded that the South Kalimantan Provincial Research and Development Agency (BPPD) has a multifunctional strategic role as a think tank and supervisor in order to foster and supervise the implementation of regional government through research and development functions. It is recommended that the district/city government form independent research and development institutions. Keywords: Research and Development Institution, Think Tanks, Local Government, Civilization Changed Acceleration and Digital Era. Abstrak Era digital ditandai dengan kemajuan perangkat teknologi digital, kehadiran big data, proses digitalisasi, serta penggunaannya secara intensif dan massif. Digitalisasi mampu menghemat waktu, menghilangkan batas-batas alamiah, mengintegrasikan ruang dan waktu pada satu momen yang sama, dan pada akhirnya merubah peradaban, memudahkan kehidupan, dan mensejahterakan manusia. Penyelenggaraan urusan pemerintahan daerah menuntut kemampuan pemerintah daerah (pemda) beradaptasi, mengakselerasi, dan menjamin kualitas layanan sesuai ritme dan peradaban era digital. Merespon dinamika ini, pemda diberi kewenangan unsur penunjang urusan pemerintahan dibidang penelitian dan pengembangan. Idealnya, penelitian dan pengembangan dilakukan oleh perangkat daerah yang mandiri dan terfokus mengelola aktivitas kelitbangan. Badan Penelitian dan Pengembangan Daerah (BPPD) selaku think tankmemiliki peran strategis menyelenggarakan urusan pemerintahan daerah termasuk pembinaan dan pengawasan penyelenggaraan pemerintahan daerah melalui fungsi penelitian dan pengembangan. Studi ini berupaya mengungkap eksistensi institusi think tankpemda di wilayah Provinsi Kalimantan Selatan. Metode yang digunakan adalah kualitatif-deskriptif dengan fokus studi BPPD Provinsi Kalimantan Selatan. Hasil analisis dan pembahasan menyimpulkan bahwa institusi kelitbangan (BPPD) Provinsi Kalimantan Selatan memiliki peran strategis dengan multifungsi selaku think tankdan supervisor dalam rangka pembinaan dan pengawasan penyelenggaraan pemerintahan daerah melalui fungsi penelitian dan pengembangan. Direkomendasikan kepada pemda kabupaten/kota agar membentuk institusi penelitian dan pengembangan yang bersifat mandiri. Kata Kunci:Institusi Kelitbangan, Think Tanks, Pemda, Akselerasi Perubahan Peradaban, dan Era Digital.